Evaluasi Kompetensi Guru Penggerak di Sekolah Dasar Kabupaten Buru Menggunakan Model CIPP - imaniar (Kelola: Jurnal Manajemen Pendidikan, 2025)
This study aims to evaluate whether the competence of the driving teacher in the category of developing oneself and others can improve the quality of elementary schools in Buru Regency and evaluate whether the competence of the driving teacher in the category of learning leadership can improve the quality of elementary schools in Buru Regency. This study is an evaluation study. The aspects that will be evaluated in this study are developing oneself & others and learning leadership. The evaluation model chosen in this study is CIPP developed by Stufflebeam, which includes context, input, process, and product. The study was conducted in four elementary schools in Buru Regency, namely SD Negeri 2 Namlea, SD Negeri 7 Namlea, SD Negeri 6 Waeapo, and SD Alhilaal Namsina with data sources being driving teachers, principals, and fellow teachers. Data collection techniques used in the study were interviews, observations, and documentation. The data validity test used triangulation of sources and techniques. Data analysis techniques include data collection, data reduction, data presentation, and data verification. Evaluation of the competence of developing oneself and others shows that driving teachers have a high awareness of developing, creating a sustainable learning environment, implementing a positive culture, and sharing good practices so as to improve school quality. The evaluation of learning leadership competency indicates that the driving teacher demonstrates learning leadership that has a positive impact on school quality. The driving teacher implements student-centered learning supported by technology, positive culture, and social emotional learning. As a result, student motivation and participation have increased significantly. Stronger support is needed from all school residents and the education office in developing competency.